Systems for the detection and processing of wave-spike type EEG signals. - Zapata Ferrer, Ángel. P.; Moncada Jiménez, Carlos; Gaona González, Andrés; Aguillón Pantaleón, Miguel Ángel (Revista Mexicana de Ingenieria Biomedica, 1991)
Epilepsy can be defined as a nervous disorder characterized by attacks that occur irregularly due to abnormal neuronal activity within the cerebral hemispheres. This affects approximately 1% of the population in our country, that is, more than 800,000 people. People of all races and ages are possible candidates for this evil. Thus, as a more accurate data it is known that 1.5% of the total population of the United States suffers from this disease.